1984
DOI: 10.1159/000176801
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-Hydroxyvitamin D and Normal Serum Calcium Concentrations in Saudi Arabia: Riyadh Region

Abstract: Serum levels of the circulating form of vitamin D, 25-hydroxyvitamin D, and calcium were measured in 104 Saudis, 44 Jordanians, 17 Egyptians and 10 other subjects aged between 18 and 23 years. All subjects were male university students living in Riyadh for more than 2 years. 25-Hydroxyvitamin D levels were (mean ± SD) 12.8 ± 6.3, 11.0 ± 5.8, 11.9 ± 6.9 and 11.9 ± 5.0 ng/ml, respectively. The percentages of subjects with serum 25-hydroxyvitamin D levels below 10 ng/ml were 35, 45, 53 and 50% for normal Saudis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
5

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 20 publications
4
80
1
5
Order By: Relevance
“…According to the data provided, 30-70% of people from different communities have varying degrees of hypovitaminosis D (Sedrani, 1984;El-Hajj Fuleihan et al, 2001;Nesby-O'Dell et al, 2002;Gordon et al, 2004;Vieth, 2004;Sullivan et al, 2005;Bodnar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…According to the data provided, 30-70% of people from different communities have varying degrees of hypovitaminosis D (Sedrani, 1984;El-Hajj Fuleihan et al, 2001;Nesby-O'Dell et al, 2002;Gordon et al, 2004;Vieth, 2004;Sullivan et al, 2005;Bodnar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In the present study, the number of people with vitamin D3 deficiency or insufficient levels of the vitamin was high …”
mentioning
confidence: 50%
“…No significant association has been found between low BMD and sun exposure. Some studies have attributed the high prevalence of osteomalacia and vitamin D deficiencies in Saudi Arabian women to their cultural practice of wearing clothing that covers the entire body and face, which could prevent direct exposure to sunlight (30,36). Other Saudi studies also found a direct positive correlation between sun exposure and serum levels of vitamin D (37).…”
Section: Discussionmentioning
confidence: 99%